Penambahan Perbedaan Waktu Dan Konsentrasi Ragi Roti Terhadap Kualitas Virgin Coconut Oil (VCO) - Jannah, Mutiatul; Ita Emilia; Panca Putri, Yunita (Indobiosains, 2025)
Research has been conducted entitled Addition of Differences in Time and Concentration of Baker's Yeast to the Quality of Virgin Coconut Oil (VCO). This research aims to analyze the addition of differences in time and concentration of baker's yeast on the quality of Virgin Coconut Oil. VCO quality testing was carried out at the Biology Laboratory, Faculty of Science and Technology, PGRI University, Palembang. The method used is the experimental method. The research results showed that the highest amount of VCO and yield were 71 ml and 35.5% respectively in the treatment with the addition of a 1% concentration of baker's yeast with a fermentation time of 24 hours. The lowest amount of VCO and yield was 10 ml and 5% in the treatment with the addition of a 3% concentration of baker's yeast for a fermentation time of 36 hours. Organoleptic tests on color, smell and taste, namely at 12 hours and 24 hours of fermentation, the VCO color is clear, the aroma is typical of coconut fruit, and the taste is savory. However, as the time and concentration of baker's yeast increases (36 hours and 48 hours), the aroma produced by VCO smells less favorable (rancid) and the color becomes cloudy.